2010
DOI: 10.1086/655659
|View full text |Cite
|
Sign up to set email alerts
|

Return of Chloroquine‐Susceptible Falciparum Malaria in Malawi Was a Reexpansion of Diverse Susceptible Parasites

Abstract: The spread of drug-resistant Plasmodium falciparum malaria has been a major impediment to malaria control and threatens prospects for elimination. We recently demonstrated the return of chloroquine-susceptible malaria in Malawi after chloroquine use was abandoned. In this study, we trace the origins of chloroquine-resistant and chloroquine-susceptible parasites in Malawi by sequencing the P. falciparum chloroquine resistance transporter gene (pfcrt) and by genotyping microsatellites flanking this gene in isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

22
120
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(144 citation statements)
references
References 40 publications
22
120
2
Order By: Relevance
“…S2). Additionally, the absence of a significant chloroquine sensitivity signal at pfcrt is consistent with reports that the return of chloroquine-sensitive parasites in Africa did not result from a classic selective sweep (26). In either case, the Manhattan-like z-score plots allow us to note the presence of these drug-sensitivity signals while keeping them visually separate from the drug resistance signals on which we wish to focus.…”
Section: Discussionsupporting
confidence: 87%
“…S2). Additionally, the absence of a significant chloroquine sensitivity signal at pfcrt is consistent with reports that the return of chloroquine-sensitive parasites in Africa did not result from a classic selective sweep (26). In either case, the Manhattan-like z-score plots allow us to note the presence of these drug-sensitivity signals while keeping them visually separate from the drug resistance signals on which we wish to focus.…”
Section: Discussionsupporting
confidence: 87%
“…In Malawi, withdrawal of chloroquine was followed by the expansion of chloroquine-sensitive parasites possessing a wild-type Pfcrt allele, apparently better fit than mutant parasites in the absence of chloroquine pressure (26,32). A similar phenomenon was reported in China (44).…”
mentioning
confidence: 56%
“…This situation contrasts with multiple settings in Africa, where the majority of molecular studies (10)(11)(12)(13) have documented an increase in the prevalence of WT pfcrt after CQ withdrawal. An analysis of the diversity of microsatellites flanking pfcrt in Malawi showed that the return to CQ susceptibility was caused by a reexpansion of the WT PfCRT haplotype (11). Such a difference between South America and other endemic regions in response to CQ withdrawal is generally attributed to other amino acid changes in PfCRT and PfMDR1 (both present on the parasite digestive vacuole membrane), which accompany the PfCRT K76T substitution.…”
mentioning
confidence: 80%
“…In South America, the prevalence of the CQR marker K76T in the drug efflux transmembrane protein PfCRT has remained high, despite CQ having been abandoned for the treatment of P. falciparum infections (7)(8)(9). This situation contrasts with multiple settings in Africa, where the majority of molecular studies (10)(11)(12)(13) have documented an increase in the prevalence of WT pfcrt after CQ withdrawal. An analysis of the diversity of microsatellites flanking pfcrt in Malawi showed that the return to CQ susceptibility was caused by a reexpansion of the WT PfCRT haplotype (11).…”
mentioning
confidence: 99%